Checklist of the Family Chironomidae (Order: Diptera) from Turkey - Tasdemir, Ayse; Akyildiz, Gurcay Kivanc (Zootaxa, 2023)
The current study presents a comprehensive taxonomic list of the Chironomidae family in Turkey. The research involved an extensive literature review, resulting in the hierarchical classification of 7 out of the 11 subfamilies. The checklist encompasses 408 chironomid taxa belonging to 128 genera. Among these, 5 are classified at the genus level, while 364 are classified at the species level. Furthermore, 17 taxa have been identified as nomen dubium, and 22 taxa have been categorized as species inquirenda. Excluding the n. dub. and sp. inq., the subfamilies contribute the following number of species: Telmatogetoninae (1 species), Podonominae (1 species), Tanypodinae (40 species), Diamesinae (15 species), Prodiamesinae (2 species), Orthocladinae (172 species), and Chironominae (133 species). This checklist serves as a valuable resource for future studies on Chironomidae biodiversity and ecological research in Turkey.